Automated Toll Collection coupled with Anti-theft & Vehicle Document Verification System using RFID and Arduino Uno - Sidhu, Neena; Jain, Akshita; Shukla, Yashashwita; Patil, TB; Sawant-Patil, ST (International Journal of Computer Sciences and Engineering, 2025)
India has a wide network of roads and transportation playing a key role in the economic development of the nation. Traditional manual collection of tax at the toll plazas doesn’t provide an efficient and effective method for management of traffic on the highways leading to heavy congestions resulting in wastage of time and resources. Therefore in the paper a system is proposed which automatic toll collection, anti- theft system along with document verification of the vehicle. A system uses radio frequency identification (RFID), Arduino Uno microcontroller, GSM SIM 800, EM 18 reader and a computer host. Passive RFIDs are widely popular for its applications in the field of transportation and they are extensively used in motor vehicles for automated toll collection. They are easy to install and work for a lifetime based on getting its power supply from a reader module. In toll plaza collection it checks for blacklisted vehicles in the centralized database and verifies the documents, to ensure whether they are up to date or expired in terms of validity. This is a step towards digital India, where all the transaction are executed in an instant ensuring smoother flow of traffic and reducing the time spent in the ques of major toll plazas across the country. The system contributes to the existing methodology by ensuring the safety of the vehicle with anti-theft feature and keeping a check on the crime rate by maintaining a stolen vehicle directory. With document verification it manages all the documents and maintains a soft copy in the database along with an archive of modified records. It ensures that all the vehicles commuting on the roads have valid papers and rules & regulation are not violated and catching hold of people driving without proper documents at the toll booth. The proposed system increases efficiency in collecting taxes, reducing traffic congestion at the toll booths and resulting in lower fuel consumption.